Composição bromatológica e coeficientes de hidrólise enzimáticas de resíduos da palmeira macaúba (Acrocomia Aculeata) - Nascimento, Welda Gonçalves do (Universidade Federal do Tocantins, 2021)
In summary the Acrocomia aculeata is a palm tree that can enjoy practically all of its natural resources, besides being easily found in practically all Brazilian territory. Based on this, through a technical cooperation work between the Federal University of Viçosa (UFV) and the Federal University of Tocantins (UFT) residues obtained from oil extraction by the cold extrusion process were used, which was carried out by UFV. In order to quantitatively evaluate and describe the chemical composition of the chemical composition of the following residues: bark + extruded mesocarp and extruded almond, along with evaluations of the hydrolysis potential of the starch fraction, and hydrolysis of fibrous carbohydrates (cellulose and hemicellulose), it was also evaluated its potential for ethanol production (first and second generation), the experiment was conducted in the Soil and Agroindustrial Waste Analysis laboratory at UFT. A completely randomized experimental design (DIC) in a 2x2 factorial scheme was used, with two extruded macaúba residues (ALMOND EXT and PEEL + MESO EXT) and two pre-treatments (with and without boiling) before the enzymatic hydrolysis of starch and cell wall, thus resulting in four treatments with five replications per treatment, totaling 20 experimental plots. The pre-treatment with boiling was of great value as it improved the potential of amylolytic and fibrolytic hydrolysis of biomass derived from macaúba processing in relation to the low content of hydrolysable starch and cellulose that were found in the biomass, the use of these to obtain ethanol may not be the best alternative for its use. As a result of this, future studies of and identification of components present in the watersoluble fractions of both biomasses may be promising for the food industry as a source of amino acids (extruded almond) and soluble fibrous and non-fibrous carbohydrates (macaúba mesocarp).